Currency Crises and Purchasing Power Parity in the Asian Countries: Evidence Based on Second-Generation Panel Unit-Root Tests - Soon, SV; Baharumshah, AZ; Shariff, NSM; Ibrahim, S (Persatuan Ekonomi Malaysia, 2024)
Indexed by WOS/ERA